Prevalence of Infectious Diseases of Migrant Workers Undergoing Health Examinations at Rajavithi Hospital - Krairitchai, Udom; Puengphrakiat, Duenpen; Arsayos, Kritsana; Boonthongtho, Kanya (Journal of Health Science of Thailand, 2017)
There is a rapidly increasing number of migrant workers coming for job opportunities in Thailand. These migrant workers often harbor some serious communicable diseases. The objective of this study was to describe the prevalence of infectious diseases in these migrant workers. This was retrospective study on migrant workers who presented for check-ups needed for work permits at Rajavithi Hospital during 1 January 2008-31 December 2010. They were examined for serious infectious diseases including pulmonary tuberculosis-TB, elephantiasis, leprosy and syphilis. Data of their health status was analyzed. A total of 102,090 migrant workers were examined. The majority of cases were female (58.4%) and 94.3 percent of the population was under 40. Workers from Myanmar constituted the most cases, (78.9%), followed by workers from Laos (14.0%) and Cambodia (7.0%). The overalol prevalence of infectious diseases in the workers was 1,612.3 cases per 100,000 population. Patients with pulmonary TB, elephantiasis, leprosy, syphilis and malaria were reported at 1,112.7, 7.8, 4.9, 465.3 and 21.5 cases per 100,000 population respectively. The prevalence of pulmonary TB in Burmese, Laotian and Cambodian workers were 1,119.3, 885.9 and 1493.2 cases per 100,000 population respectively. The prevalences of syphilis in Burmese, Laotian and Cambodian workers were 467.8, 258.1 and 851.2 cases per 100,000 population respectively. Migrant workers with infectious diseases amounted to 1,612.3 cases per 100,000 population. Those harboring these serious transmitted diseases may be a leading factor in their potential widespread in Thailand.